Film Dokumenter Sexy Killers Sebagai Alat Kritik Kandidat dalam Pemilihan Presiden 2019 - Yugha Erlangga (Badan Pengawas Pemilihan Umum, 2019)
This writing is based on the increasing variety of criticism deliveries to the candidates of 2019 Presidential Election; one of them is through a documentary titled Sexy Killers. The film produced by Watchdoc production house and directed by a senior journalist, Dandhy Dwi Laksono, is the second work that welcomes the election season, after in 2014 they released a documentary Yang Ketu7uh. Sexy Killers is a creative product that contains criticism on the ruler’s policies—one that competed in 2019 Presidential Election. Witnessing the development of the digital world, one of them is the existence of Youtube channel, the public access to Sexy Killers is easier. The existence of Sexy Killers is inevitable in democracy because of the openness of public space. This writing will measure the length of how a creative product, such as a documentary, can influence the discourse in public space towards the candidates in the election. This research uses a descriptive analytical method. The data collection is also done by interviewing Dandhy Dwi Laksono as the director. This writing is also supported by the media study and other literature that contain the debate and polemic of Sexy Killers’s existence in public. The finding of this writing shows that Sexy Killers, which up to July 2019 has been accessed by approximately 24 million viewers, is capable in giving the effect in returning a substantial discourse to the public space in the middle of satiety on debate issues between the candidates of 2019 Presidential Election.